History and developments of pastoral care in Africa: A survey and proposition for effective contextual pastoral caregiving - Magezi, Vhumani (HTS teologiese studies, 2019)
The practice of pastoral care (cura animarum) over the ages has been informed and influenced by the need to develop creative ways (interventions) to respond to people’s contextual challenges. These approaches have been well documented. However, the history, developments and emerging pastoral care practices in Africa have not been documented. This article, by way of a survey, considers the pastoral care approaches that emerged in Africa from the period when Christianity was introduced to the continent. It addresses three interlinked questions. Firstly, to what extent has pastoral care approaches and practices in Africa been influenced by the African context and developments? Secondly, to what extent has the context and the emerging pastoral care approaches in Africa been discerned from historical developments and documented? Thirdly, what links can be drawn between pastoral care practices in Africa and its historical as well as cultural context? In answering these questions, the article retrieves pastoral care developments in Africa by discerning pastoral care during the periods of Christianity in Africa. The notion of cura animarum as ‘soul care’, referring to care for the whole person (holistic care, i.e., nephesh care) from a Christian spiritual perspective, will be employed as a framework. The assumption guiding the article is that pastoral care practices and approaches in Africa have arisen as responses to the contextual realities being experienced at the interface of Christianity and the African people. These realities arose and persist to this day as a struggle to relate, apply and live out an authentic African Christian life to cope with life in a meaningful way. It concludes by suggesting ways on how pastoral care in Africa should be practiced in the current period and going forward.